Lipid Levels and 3-Month Prognosis After Spontaneous Intracerebral Hemorrhage in Women - Feng, Hao; Wang, Xin; Wang, Wenjuan; Zhao, Xingquan (Frontiers in Neurology, 2021)
Background: The relationship between serum lipids levels and prognosis after spontaneous intracerebral hemorrhage (ICH) is still unclear. We aim to examined the association between lipid levels and 3-month ICH prognosis in women. Method: We went through a registry of spontaneous ICH cases and selected female patients to study according to our criteria.. We collected demographic, clinical and laboratory information and evaluated serum triglyceride (TG) levels, total cholesterol (TC) levels, low-density cholesterol (LDLC) levels, high-density cholesterol (HDLC) levels, non-high-density cholesterol (non-HDLC) levels and 3-month modified Rankin Scale (mRS). Multivariate logistic regression was performed and receiver operating characteristic (ROC) curves were plotted to explore the relationship between serum lipid levels and 3-month ICH clinical outcomes. Results: 206 female patients were included in this study and 96 (46.6%) of them had poor functional outcomes. In the univariate analysis, low TG (p=0.006), TC (p=0.025), LDLC (p=0.001), non-HDLC (p< 0.001) levels and high HDL (p=0.036) levels were associated with poor 3-month clinical outcomes in women. In the multivariate logistic regression, low levels of TG (OR=0.711, 95%CI=0.542-0.933, p=0.014), TC (OR=0.523, 95%CI=0.304-0.903, p=0.020), LDLC (OR= 0.538, 95%CI=0.307-0.942, p=0.030), non-HDLC (OR=0.327, 95%CI=0.177-0.603, p<0.001) and high level of HDLC (OR=2.075, 95%CI=1.064-4.047, p=0.032) with area under the curve (AUC) were 0.610, 0.590, 0.630, 0.645 and 0.415, respectively, remained as independent indicators of poor prognosis at 3 months after adjusting for confounding factors. Conclusion: Low levels of TG, TC, LDLC, non-HDLC and high levels of HDLC were independently associated with poor prognosis of spontaneous ICH in women.